Selenium in cancer management: exploring the therapeutic potential - He, Lingwen; Zhang, Lu; Peng, Yulong; He, Zhijun (Frontiers in Oncology, 2025)
Selenium (Se) is important and plays significant roles in many biological processes or physiological activities. Prolonged selenium deficiency has been conclusively linked to an elevated risk of various diseases, including but not limited to cancer, cardiovascular disease, inflammatory bowel disease, Keshan disease, and acquired immunodeficiency syndrome. The intricate relationship between selenium status and health outcomes is believed to be characterized by a non-linear U-shaped dose-response curve. This review delves into the significance of maintaining optimal selenium levels and the detrimental effects that can arise from selenium deficiency. Of particular interest is the important role that selenium plays in both prevention and treatment of cancer. Finally, this review also explores the diverse classes of selenium entities, encompassing selenoproteins, selenium compounds and selenium nanoparticles, while examining the mechanisms and molecular targets of their anticancer efficacy.